Economics Journals as a Communications Network - Eagly, Robert V. (Journal of Economic Literature, 1975)
This study is part of a larger project that was originally conceived to examine the communications function of economics journals for the period since 1890. Research was begun in 1967 and was continued intermittently in the intervening years. The materialfocusing on the periods 1961-64 and 1970-71 was drafted in preliminary form in 1972 and in final form in early 1974. Work dealing with the earlier years remains still in progress. I wish to give my thanks to the several persons whose research assistance was indispensible over the many years of the project. They include Lawrence Cavanagh, Frederick Garzino, Shirley Chiou, Roslind Diamond, and Robert McDougal. I am especially grateful to the editors and reviewers for their comments on the manuscript. The views expressed are those of the author and not of the Federal Reserve Bank of New York.